The hydraulic system of Uxul : origins, functions, and social setting - Seefeld, Nicolaus, (Archaeopress pre-Columbian archaeology., 2018)
This research seeks to close an essential research gap - the understanding of the water management strategies of the Maya in pre-Hispanic times. It focuses on the archaeological investigation of the hydraulic system of Uxul, a medium-sized Maya centre in the south of the state of Campeche, Mexico.